2004
DOI: 10.1094/cchem.2004.81.5.666
|View full text |Cite
|
Sign up to set email alerts
|

End Use Quality of Waxy Wheat Flour in Various Grain‐Based Foods

Abstract: Cereal Chem. 81(5):666-672The practical applications of flour from waxy (amylose-free) hexaploid wheat (Triticum aestivum L.) were assessed. The applications evaluated were bread, cakes, white salted noodles, and pasta for gyoza. An excessive addition of waxy hexaploid wheat flour to total wheat flour (>20%) resulted in poorer functional properties (sticky, lumpy, or less crispy textures) in almost every end use product. However, incorporation of <20% waxy hexaploid wheat flour, produced considerable improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 16 publications
4
54
0
2
Order By: Relevance
“…Those starch properties are related to less amylose content Zeng et al 1997). However, although showing higher breakdown and higher swelling power than conventional starches, flours made from waxy wheat (no waxy protein, 0 % amylose) were found not suitable for making noodles, being sticky, extremely soft upon cooking, and did not maintain the integral structure of the noodle strands (Baik and Lee 2003;Hayakawa et al 2004). The use of partial waxy lines (flour with reduced amylose content, around 15-19 %) or flours blend with waxy flour (30-50 %) seems to be more suitable for that product as showed by .…”
Section: Effect Of Wx Gene Mutations On Amylose Content and End-use Qmentioning
confidence: 99%
See 2 more Smart Citations
“…Those starch properties are related to less amylose content Zeng et al 1997). However, although showing higher breakdown and higher swelling power than conventional starches, flours made from waxy wheat (no waxy protein, 0 % amylose) were found not suitable for making noodles, being sticky, extremely soft upon cooking, and did not maintain the integral structure of the noodle strands (Baik and Lee 2003;Hayakawa et al 2004). The use of partial waxy lines (flour with reduced amylose content, around 15-19 %) or flours blend with waxy flour (30-50 %) seems to be more suitable for that product as showed by .…”
Section: Effect Of Wx Gene Mutations On Amylose Content and End-use Qmentioning
confidence: 99%
“…The use of partial waxy lines (flour with reduced amylose content, around 15-19 %) or flours blend with waxy flour (30-50 %) seems to be more suitable for that product as showed by . This could be also used to prepare more increased staling-and freezing-tolerant grain-based foods (Hayakawa et al 2004).…”
Section: Effect Of Wx Gene Mutations On Amylose Content and End-use Qmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial firmness of bread is associated with the fast gelation properties of amylose during cooling of bread. 67 Hayakawa et al 68 observed a softening of bread texture with the incorporation of 5-30% waxy wheat flour and noted that waxy wheat flour may potentially delay retrogradation. Waxy barley starches have also been reported to have very slow retrogradation kinetics.…”
Section: Enrichment Of Sponge-and-dough Bread With Frf and Incorporatmentioning
confidence: 99%
“…However, the inferior quality of whole grain breads is still significant issue and the scientific efforts to improve the quality of whole grain foods are being done. Recently, waxy (amylose-free) wheat grains, which were produced by new physicochemical and biological techniques, were reported to have the superior properties to apply for breadmaking with retardation of staling and extended shelf life of breads, and formation of a new texture of breads with soft, viscous and glutinous breadcrumbs (Hayakawa, Tanaka, Nakamura, Endo, & Hoshino, 2004;Morita et al, 2002a). Therefore, waxy wheat used for whole grain food processing is believed to improve the functional properties of bread.…”
Section: Introductionmentioning
confidence: 99%